2014 IEEE Frontiers in Education Conference (FIE) Proceedings 2014
DOI: 10.1109/fie.2014.7044368
|View full text |Cite
|
Sign up to set email alerts
|

Student performance in first year, mathematics, and physics courses: Implications for success in the study of electrical and computer engineering

Abstract: Abstract-Mathematics and physics courses are recognized as a crucial foundation for the study of engineering, and often are prerequisite courses for the basic engineering curriculum. But how does performance in these prerequisite courses affect student performance in engineering courses?This study evaluated the relationship between grades in prerequisite math and physics courses and grades in subsequent electrical engineering courses. Where significant relationships were found, additional analysis was conducte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 7 publications
2
2
0
Order By: Relevance
“…Results from the conditional probability approach and ordinal regression have confirmed that when a student receives a C in a link, they will have the exact probability of getting either DFW or ABC in the next link within the chain. Simpson and Fernandez’s (2014) results are nearly comparable with this result’s findings that C+ is an indication grade for getting higher grades in the subsequent course.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Results from the conditional probability approach and ordinal regression have confirmed that when a student receives a C in a link, they will have the exact probability of getting either DFW or ABC in the next link within the chain. Simpson and Fernandez’s (2014) results are nearly comparable with this result’s findings that C+ is an indication grade for getting higher grades in the subsequent course.…”
Section: Discussionsupporting
confidence: 87%
“…Krause-Levy et al (2020) found that in the organizational behavior course, the grade in the prerequisite was positively related to subsequent performance. Simpson and Fernandez (2014) investigated how mathematics and physics (prerequisite courses) overall scores affect the subsequent electrical and computer engineering (ECE) courses at Indiana University-Purdue University Indianapolis. In addition, they examined how Calculus (I) overall scores affect student performance in Calculus (II).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Simpson and Fernandez performed research on a dataset that is similar to the one presented in this paper to identify if strong correlations exist between students' grades during their early semesters and their corresponding performance in mid-level engineering courses. They used a linear correlation instead of a monotonic correlation, as presented in this paper, but found the same conclusion of prerequisite course performance having a strong correlation with the performance in the requisite course [6]. Similar conclusions are found by Hwang, Yu, Su and Tseng [7] in their research on undergraduate students who participated in programming courses, through the use of fuzzy logic association rules.…”
Section: Literature Reviewsupporting
confidence: 77%
“…Simpson and Fernandez [130] analyzed student performance in first-year math and physics courses in the study of electrical and computer engineering (ECE). They focused on answering the question: "how does performance in these prerequisite courses affect student performance in engineering courses?"…”
Section: Assessment Methodsmentioning
confidence: 99%